1996
DOI: 10.1073/pnas.93.17.8956
|View full text |Cite
|
Sign up to set email alerts
|

FRAG1, a gene that potently activates fibroblast growth factor receptor by C-terminal fusion through chromosomal rearrangement.

Abstract: A constitutively active form of fibroblast growth factor 2 (FGFR2) was identified in rat osteosarcoma (ROS) cells by an expression cloning strategy. Unlike other tyrosine kinase receptors activated by N-terminal truncation in tumors, this receptor, FGFR2-ROS, contains an altered C terminus generated from chromosomal rearrangement with a novel gene, designated FGFR activating gene 1 (FRAGJ). While the removal of the C terminus slightly activates FGFR2, the presence of the FRAGI sequence drastically stimulates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 24 publications
4
41
0
Order By: Relevance
“…Together with other known variants, K-SAM-IIC3 (Itoh et al, 1994) and KGFR-ET (Lorenzi et al, 1996), our ®ndings suggest that four KGFR isoforms with di erent C-termini are generated by alternative splicing (Figure 6a). The C-terminal domain of K-SAM-IIC3 is encoded by the C3 exon, which contains a translation termination codon and polyadenylation sequence (Itoh et al, 1994).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Together with other known variants, K-SAM-IIC3 (Itoh et al, 1994) and KGFR-ET (Lorenzi et al, 1996), our ®ndings suggest that four KGFR isoforms with di erent C-termini are generated by alternative splicing (Figure 6a). The C-terminal domain of K-SAM-IIC3 is encoded by the C3 exon, which contains a translation termination codon and polyadenylation sequence (Itoh et al, 1994).…”
Section: Discussionsupporting
confidence: 76%
“…We have previously found that alterations of the Cterminus of KGFR/FGFR2 can stimulate the receptor's transforming activity (Lorenzi et al, 1996). Therefore, we examined a possibility that PA-1 parathyroid adenoma might express KGFR with a similar C-terminal variation.…”
Section: Kgfr-pa Contains An Altered C-terminusmentioning
confidence: 98%
See 2 more Smart Citations
“…Whether this increased transforming ability resulted from higher steady state levels of the Axl protein or a functional di erence of the chimeric receptor is unclear. Possible mechanisms for this augmented transforming ability include enhanced protein stability, altered substrate selection, perturbation of receptor turnover, and altered intramolecular interactions (Kornilova et al, 1996;Lorenzi et al, 1996;O'Connor et al, 1997). Nevertheless, it remains consistent that transformation by any form of Axl is associated with receptor overexpression.…”
Section: Discussionmentioning
confidence: 99%